Cultural collectivism, intimate partner violence, and women's mental health: An analysis of data from 151 countries - Rajkumar, Ravi Philip (Frontiers in Sociology, 2023)
Culture, defined as the distinctive, learned beliefs and patterns of behavior that are particular to a given group or community, is a key determinant of mental health. The cultural dimension of individualism-collectivism, which measures the extent to which a given society accords importance to individuals as opposed to larger groups, has been associated with cross-national variations in mental health outcomes such as depression and suicide. However, this cultural dimension is also associated with variations in the frequency of intimate partner violence (IPV), which has a significant and sustained adverse impact on women’s mental health. This study examines the relationships between individualism-collectivism, the frequency of IPV, and rates of depression and suicide in women, based on data from 151 countries. In this data set, IPV was significantly associated with age-standardized rates of depression and suicide in women, even after adjusting for demographic variables. Cultural collectivism was positively correlated with IPV, but this relationship was significantly influenced by national income and women’s educational attainment. In multivariate analyses, IPV, but not cultural collectivism, remained significantly associated with depression in women. These results highlight the importance of screening for and addressing IPV in women seeking mental health care, particularly in low- and middle-income countries where cultural and economic factors may both increase the risk of IPV and delay or impede its reporting.